Appliance of Social Return of Investment (SROI) for Valuable Evaluation of Sustainable Development Goals (SDGs) at Village-Owned Enterprises (BumDes) Bumi Arum Tlahab Village, Kledung District, Temanggung Regency - Purbawati, Dinalestari; Achmad, Tarmizi; Raharja, Surya; Ainuddin, Ilham (Jurnal Administrasi Bisnis, 2025)
This study is grounded in the growing importance of evaluating social, economic, and environmental impacts of community-based development programs, particularly in the context of rural tourism recovery following the COVID-19 pandemic. Village-Owned Enterprises (Bumdes) play a strategic role in optimizing local potential; however, systematic approaches to measure their broader impacts remain limited. This research aims to apply the SROI method in evaluating and planning future activities for the Bumdes Bumi Arum Tlahab’s program. The measurements of the effectiveness of Bumdes Bumi Arum through SROI focuses on managing Posong natural tourism in 2023. Based on the calculation results, it shows that the SROI ratio at Bumdes Bumi Arum Tlahab is 1.46, which means that each investment is IDR 1 is capable of producing an impact or benefit of IDR 1.46,-. If viewed from a socio-economic perspective, the activities of Bumdes Bumi Arum can be said to be feasible and successful because the calculation results show that the SROI value is more than one and is positive. These results suggest that SROI is a relevant and practical tool for assessing the multidimensional impacts of village-based enterprises and aligning them with sustainable development objectives. It is recommended that practitioners enhance data accuracy and adopt continuous evaluation practices, while policymakers support the broader implementation of SROI frameworks in rural development programs. Future research should develop context-specific models and expand comparative studies to strengthen the robustness and applicability of SROI in diverse community settings.